American Society for Parenteral and Enteral Nutrition and Academy of Nutrition and Dietetics: Revised 2014 Standards of Practice and Standards of Professional Performance for Registered Dietitian Nutritionists (Competent, Proficient, and Expert) in Nutrition Support. (1st November 2014) - Brantley, Susan L.; Russell, Mary K.; Mogensen, Kris M.; Wooley, Jennifer A.; Bobo, Elizabeth; Chen, Yimin; Malone, Ainsley; Roberts, Susan; Romano, Michelle M.; Taylor, Beth
Abstract : This 2014 revision of the Standards of Practice (SOP) and Standards of Professional Performance (SOPP) for Registered Dietitians Nutritionists (RDNs) in Nutrition Support represents an update of the 2007 Standards composed by content experts of the American Society for Parenteral and Enteral Nutrition and the Academy of Nutrition and Dietetics. The revision is based upon the Revised 2012 SOP in Nutrition Care and SOPP for RDs, which incorporates the Nutrition Care Process and the six domains of professionalism: Quality in Practice, Competence and Accountability, Provision of Services, Application of Research, Communication and Application of Knowledge, and Utilization and Management of Resources. These SOP and SOPP are designed to promote the provision of safe, effective, and efficient nutrition support services, facilitate evidence‐based practice, and serve as a professional evaluation resource for RDNs who specialize or wish to specialize in nutrition support therapy. These standards should be applied in all patient/client care settings in which RDNs in nutrition support provide care. These settings include, but are not limited to, acute care, ambulatory/outpatient care, and home and alternate site care. The standards highlight the value of the nutrition support RDN's roles in quality management, regulatory compliance, research, teaching, consulting, and writing for peer‐reviewed professional publications. The standards assist the RDN in nutrition support to distinguish his or her level of practice (competent, proficient, or expert) and would guide the RDN in creating a personal development plan to achieve increasing levels of knowledge, skill, and ability in nutrition support practice.